Influence of the options for the induction of general anesthesia for elective abdominal delivery on condition of newborns - A. N. Biryukov; A. G. Klimov; E. N. Ershov; O. V. Pashchenko (Медицинский вестник Юга России, 2019)
Objective: to evaluate and compare the influence of the options for the induction of general anesthesia for elective abdominal delivery on the condition of newborns. Materials and Methods: The study included 160 newborns, which were born via elective cesarean section under general anaesthesia. All newborns were divided into 4 groups, 40 in each, depending on the anesthetics used for the induction of general anesthesia. In the 1st group, thiopental sodium 5 mg/kg was used; in the 2nd - sodium thiopental 7 mg/kg; in the 3rd - propofol 2,5 mg/kg; in the 4th- sodium thiopental 5 mg/kg with sevoflurane (0,5 MAC). The influence of anesthesia on condition of newborns was evaluated by the Apgar scale and the neurological and adaptive capacity scale NACS.Results: statistically significant differences were not found in assessing newborns on scales. Conclusion: All the researched drugs and their doses used for the induction of general anesthesia during elective abdominal delivery do not adversely effect on the neurological and somatic status of the newborn.